1997
DOI: 10.1177/1358863x9700200404
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Raynaud's Phenomenon in a General Population: The Framingham Study

Abstract: The prevalence and predisposing conditions for primary and secondary Raynaud's phenomenon (RP) were examined in The Framingham Study based on 16 years of follow-up of a cohort of 4182 men and women. The association with atypical chest pain and migraine headache was also investigated.Over the 16 years of follow-up there were 130 men and 171 women who developed primary RP. The prevalence in women (9.6%) was somewhat higher than in men (8.1%) and 81.4% of the RP was primary. Secondary RP was equally prevalent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 41 publications
(4 reference statements)
0
49
0
8
Order By: Relevance
“…Over the years, we have observed patients in whom RP was present before CTS, others in whom RP developed after CTS, and others who underwent surgical decompression of the median nerve which resolved the CTS but not the RP symptoms. Although CTS and RP are more frequent in the female sex, there is a dierent ratio between the sexes, 4:1 for CTS and 2:1 for RP, and a dierent age of onset, 50±60 years for CTS and 20± 40 years for RP [2,17,22]. Many of the above papers and the present clinical observations suggest that the association between idiopathic RP and CTS may be random.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Over the years, we have observed patients in whom RP was present before CTS, others in whom RP developed after CTS, and others who underwent surgical decompression of the median nerve which resolved the CTS but not the RP symptoms. Although CTS and RP are more frequent in the female sex, there is a dierent ratio between the sexes, 4:1 for CTS and 2:1 for RP, and a dierent age of onset, 50±60 years for CTS and 20± 40 years for RP [2,17,22]. Many of the above papers and the present clinical observations suggest that the association between idiopathic RP and CTS may be random.…”
Section: Discussionmentioning
confidence: 68%
“…In fact, the Framingham study of Boston, which had a follow-up of 16 years and a cohort of 4182 subjects, showed an association of 10.5% between RP and CTS in RP patients [2]. A French epidemiological study drew similar conclusions [3].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, the sustained depressor effect of vanylidilol may be related to its ß-adrenoceptor blocking action and other vasorelaxant mechanisms. The vasoconstrictor effect of tradi-tional ß-blockers, impairment of the peripheral circulation, including Raynaud's syndrome, often occurs during treatment [29]. Therefore, vanylidilol may have therapeutic efficacy advantages over propranolol [30].…”
Section: Discussionmentioning
confidence: 99%
“…These features define Raynaud's phenomenon, a disease described first by Maurice Raynaud in 1862 (Raynaud, 1862). Raynaud's phenomenon is regarded as a rare disease; however, it is in fact commonly encountered clinically and affects between 3 and 10% of the general population, with a higher incidence in women (Brand et al, 1997;Prete et al, 2014). Although Raynaud's phenomenon was described 150 years ago, a specific treatment is still missing today.…”
Section: Introductionmentioning
confidence: 99%